Effect of heat transfer on an angled cavity placed in supersonic flow. (October 2019) - Vishnu, A.S.; Aravind, G.P.; Deepu, M.; Sadanandan, R.
Highlights: Effect of heat transfer on alterations of angled cavity flow physics is explored. Cavity tone variations with heat addition are explored in detail. A new type of wave formation is observed due to the heat addition. Abstract: Experimental and numerical studies on the effect of heat transfer to an open cavity placed in supersonic crossflow are presented. Cavity floor is subjected to the desired amount of heat flux and the consequent effects in the flow dynamics inside the cavity and its neighborhood are systematically assessed. Cavity flowfield has been visualized using high-speed Schlieren imaging and pressure on the cavity floor has been measured using both steady and unsteady pressure transducers. Two-dimensional unsteady compressible turbulent flow field has been numerically simulated using a Harten-Lax-van Leer-Contact (HLLC) scheme based unstructured finite volume method solver. The numerical method has been validated using both experimental data available in the literature as well as the wall pressure measured in the present study. Significant changes in flow dynamics such as the growth of the recirculation region, shearlayer oscillation, shearlayer impingement on the aft wall of the cavity, and frequency of cavity induced oscillations have been observed. Experimental observations are well complemented by the numerical studies and could reveal the physics of alteration in cavity flow dynamics with the heat addition.